The first collapse of the state of Asamani by turkish AL-qara- khanin in 382A.H/ 992A.M. (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This course treats the first collapse of the state of Asamani by turkish AL-qara- khanin in 382A.h/ 992A.m. When that state became weak at its last age, it entered inside the greed of turk,s circle. Thus, they shot groups of armies on their lands for controling on them and stealing them. But they didn,t stop their greed at that side. They tried to occupy Bukhra, the capital of that state and to destroy its roll on the politics yard in the Islamc east. They occupied it twice: the first one was in 382A.h/ 992A.m, when Haroun Ibn Sulaman Burkhra khan  AL-qara- khani occupied it. But, he left of it after few months, and he died on the road to Turkstan. And this allows the occasion for the Asamani Prince Nough Ibn Mansour for returning to his attend and he returned the lost Kingdom. But the life of Asamani state was disorder and horror after that returning, it didn't stay for a long time, if it didn't last for more than seven years, it would fall by turkish AL-qara-khanin from the new point in 389A.h/ 999A.m, and this was the second, and the final collapse of that state. يعالج هذا البحث سقوط الدولة السامانية الأول بيد الترك القراخانيين سنة 382هـ/ 992م، فعندما ضعفت تلك الدولة في أواخر عصرها، دخلت ضمن دائرة أطماع الترك القراخانيين، فصاروا يشنون الحملات على أراضيها للسيطرة عليها ونهبها، ولم تقف أطماعهم عند ذلك الحد، بل سعوا لاحتلال بخارى عاصمة تلك الدولة، وإنهاء دورها على الساحة السياسية في المشرق الإسلامي، فكان أن احتلوها مرتين: أما الأولى، فكانت في سنة 382هـ/ 992م، حين احتلها هارون بن سليمان بغراخان القراخاني، ولكنه لم يلبث أن انسحب منها بعد عدة أشهر، وتوفي في الطريق إلى تركستان، ما أتاح الفرصة للأمير الساماني نوح بن منصور للعودة إلى حاضرته، واستعادة ملكه الضائع، ولكن حياة الدولة الساماينة بعد تلك العودة كانت قلقة ومضطربة، ولم تعمر طويلاً، إذ لم تستمر أكثر من سبع سنوات، لتسقط من جديد بأيدي القراخانيين في سنة 389ه/ 999م، وهو السقوط الثاني والنهائي لتلك الدولة.